Peroxisome-dependent transcription factors respond to biotic and abiotic stresses in Arabidopsis and tomato - Alejandro Rodríguez-González; Laura C. Terrón-Camero; Zhivko Minchev; Luisa M. Sandalio; María José Pozo; María C. Romero-Puertas (Plant Stress)
Plants adapt to environmental challenges through complex mechanisms. They rapidly activate metabolic pathways in response to stress, relying on signaling molecules such as reactive oxygen species (ROS) for cell-to-cell communication. Peroxisomes, key subcellular organelles that regulate ROS metabolism and signaling, house a wide enzymatic antioxidant system including catalases (CAT) and the ascorbate-glutathione cycle enzymes. This study identifies a set of catalase-dependent transcription factors (TFs) transcriptionally regulated during abiotic and biotic stress responses in Arabidopsis. Additionally, it examines whether their regulation is conserved in an important crop like tomato, aiming to deepen our understanding on the functions of peroxisomes in plant stress responses. The orthologues of these Arabidopsis TFs in tomato were all regulated under stress, responding to different adverse conditions, including salt and heat stress, and pathogen and/or herbivore attack, supporting their conserved functionality in stress responses. The results pinpoint these selected TFs, regulated in response to multiple stresses in Arabidopsis and tomato, as targets for biotechnological applications to enhance crop resilience to cope with climate change challenges.